Appropriateness of fecal immunochemical testing utilization for colorectal cancer screening at an academic center. Issue 1 (2nd January 2023) - Masood, Umair; Bernshteyn, Michelle; Pavelock, Natalie; Singh, Kuldip; Schad, Laura A.; Morley, Christopher P.; Gupta, Anand; Jasti, Venkata; Murthy, Uma
Abstract: Fecal immunochemical testing (FIT) has become the most utilized test for colorectal cancer (CRC) screening. This retrospective quality assurance report analyzed data for 411 patients from one academic center in Central New York who underwent FIT between September 2015 and September 2016. All 67 positive tests and 344 of 952 negative tests were analyzed. Subjects from the FIT-negative "control group" were chosen at random. The mean age was 67 years and the male/female distribution was 391/20, with differences between the FIT-positive and -negative groups. FIT was inappropriately used in 210 (51%) of the 411 patients. The most common reasons for inappropriate FIT use were a documented refusal of colonoscopy (39.60% of inappropriate use), FIT occurring within the recommended surveillance interval from previous colonoscopy (27.98%), and a Charlson Co-Morbidity Index score ≥5 (22.87%). Other reasons were a history of adenoma (9.25%), family history of CRC/high-risk adenoma <60 years of age (5.84%), active/overt gastrointestinal bleed (4.87%), history of CRC (1.46%), and history of inflammatory bowel disease (1.46%). The results of this study show that FIT is being utilized inappropriately about 50% of the time.